HOW SUSTAINABLE BEHAVIOUR CREATES HAPPINESS: THE PERSPECTIVES OF MILLENIAL GENERATIONS - Merinda Pandowo (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this paper is to develop aninclusive model of sustainability behaviour involvepro sustainable orientation, behavioural intention, and happiness as consequence of it. 182 participants were used in this study taken by purposive sampling which is a bachelor student. The relationships between constructs are measured after all the instruments are eligible through validity and reliability testing. The examinations were used path analysis in assessing relation among constructs.The study found that sustainable behaviour is positively predicted by pro orientation behaviour and behavioural intention. Further, all constructs affect happiness directly. The recent study contributes to extend green behaviour literatures and explore the applicability of these literatures for young generations.The implication of this study is to endorse both leaders and stakeholders to apply green life since early age. Keywords: pro sustainable orientation, behavioural intention, sustainability behaviour, happiness